INVESTIGATION ON LACTOSE FERMENTING YEASTS ACTIVITY IN THE WHEY OBTAINED BY COAGULATION OF MILK PROTEINS BY BERRY COAGULANT - Olena GREK (Stefan cel Mare University of Suceava, 2017)
The results of biochemical activity of lactose fermenting yeasts in the wort based on whey, obtained by thermo acid coagulation of milk by berry raw material (sterilized black currant paste) are shown. The extraction of black currant’ valuable components occur in the protein foundation and colored whey, which can be used in the production of fermented beverages with high biological and nutrition value. It was found from the analysis of lactose fermenting yeasts’ biomass accommodation that the biggest growth of yeasts in the wort based on colored whey was in the samples which are fermented by Zygosaccharomyces lactis 868-K – the general amount of cells was (78.1...79.9)∙106 CFU/ml for 48 hours. The optimal fermentation temperature (30…32 °C) was established by the parameters of fermentation activity: accumulation of ethyl alcohol and carbon dioxide in the wort, the total amount of yeasts cells.The obtained results were used in the technology development of non-alcocholic beverages based on colored whey.